Creep failure of a steam pipe girth weld and NDT strategy on creep damage. (October 2019) - Song, Ming; Xu, Tong; Yuan, Keyi; Yu, Haiyang; Sun, Chao
Abstract: 12Cr1MoV is a commonly used heat-resistant steel for the steam pipelines of subcritical power boilers in China. Usually, the girth weld joints are the weakest areas of the entire steam pipelines. In this work, a leakage failure of girth weld joint in a 12Cr1MoV steam pipe with about 10 years' service was analyzed. The crack is along the intercritical heat affected zone (ICHAZ) in the hoop direction, and the fracture completely duplicating the geometry of the fusion line. The microstructure had degraded seriously by carbides spheroidization. In the region of ICHAZ and FGHAZ (type IV zone), creep cavities were observed along the grain boundaries. These phenomena indicate the weld joint had suffered type IV creep cracking. The formation and accumulation of the cavities in type IV zone of the weld joint before cracking is a unique phenomenon of creep. Therefore, the proper NDT method and signal extraction with strong ability on cavities recognition should be the key points for detecting the creep damage in early stage. The sensitivity and selectivity of the signal are both important for the practical application on the creep inspection. Highlights: The type IV cracking of 12Cr1MoV stream pipe girth weld was analyzed. Creep cavities was observed to distribute at ICHAZ/FCHAC in wideness of 400–500 μm. Creep detection by NDT should avoid the microstructure dependence as much as possible. The NDT with high sensitivity & selectivity just on the creep cavities is recommended.